2020
DOI: 10.1017/jfm.2020.638
|View full text |Cite
|
Sign up to set email alerts
|

Near- and far-field structure of shallow mixing layers between parallel streams

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…Although the present paper does not report validation simulations for shallow MLs developing between non-parallel streams in constant-depth channels, the same flow solver was extensively validated to predict shallow wakes and shallow MLs with α = 0° in constant-depth channels (Zeng & Constantinescu 2017; Cheng & Constantinescu 2020). Directly relevant for the present study, Cheng & Constantinescu (2020) conducted simulations for shallow MLs developing between parallel streams in a straight open channel. They showed that the numerical predictions of the streamwise velocity profiles across the ML, the velocity spectra inside the ML, the streamwise variations of the ML thickness and of the transverse shift of the ML centreline closely matched data from laboratory experiments.…”
Section: Numerical Methods and Simulation Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the present paper does not report validation simulations for shallow MLs developing between non-parallel streams in constant-depth channels, the same flow solver was extensively validated to predict shallow wakes and shallow MLs with α = 0° in constant-depth channels (Zeng & Constantinescu 2017; Cheng & Constantinescu 2020). Directly relevant for the present study, Cheng & Constantinescu (2020) conducted simulations for shallow MLs developing between parallel streams in a straight open channel. They showed that the numerical predictions of the streamwise velocity profiles across the ML, the velocity spectra inside the ML, the streamwise variations of the ML thickness and of the transverse shift of the ML centreline closely matched data from laboratory experiments.…”
Section: Numerical Methods and Simulation Set-upmentioning
confidence: 99%
“…The length scale in the simulations was D = 0.067 m. The mean bulk velocity of the flow in the two incoming streams was the same in all the simulations and was used as velocity scale. The velocity and length scales correspond to the base case in the numerical study of shallow MLs developing between parallel streams conducted by Cheng & Constantinescu (2020) and to one of the two test cases studied experimentally by Uijttewaal & Booij (2000). Most simulations were performed with a flow depth H = D , but additional simulations were performed for a symmetric confluence ( α = 60° and VR = 2.2) with H = D /2 and H = 2 D (table 1) to investigate the effect of flow shallowness.…”
Section: Numerical Methods and Simulation Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical model was also found to accurately predict the spatial development of shallow mixing layers forming in open-channel flows and the characteristics of the mixing layer vortices (e.g. size, shape, non-dimensional passage frequency) over the initial regime and over the quasi-equilibrium regime where the mixing layer undergoes stabilization due to the effect of bed friction on the mixing layer vortices (Cheng & Constantinescu 2020). Directly relevant for the present investigation, the numerical model was validated for flow past an emerged circular array of solid cylinders by Chang et al .…”
Section: Numerical Model and Test Casesmentioning
confidence: 99%
“…Except for very small values of , the cores of the shear layer eddies penetrate only partially inside the array. In the case of an array placed in a shallow open channel, the spatial development of the horizontal shear/mixing layer is expected to be affected by bed friction once the size of the vortices becomes comparable with the channel depth (Chu & Babarutsi 1988; Cheng & Constantinescu 2020). For long arrays, this leads to a stabilization of the layer growth (e.g.…”
Section: Introductionmentioning
confidence: 99%